2015
DOI: 10.5194/tcd-9-6581-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glaciological and geodetic mass balance of ten long-term glaciers in Norway

Abstract: Abstract. The glaciological and geodetic methods provide independent observations of glacier mass balance. The glaciological method measures the surface mass balance, on a seasonal or annual basis, whereas the geodetic method measures surface, internal and basal mass balances, over a period of years or decades. In this paper, we reanalyse the 10 glaciers with long-term mass balance series in Norway. The reanalysis includes (i) homogenisation of both glaciological and geodetic observation series, (ii) uncertain… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 32 publications
(41 reference statements)
3
14
0
Order By: Relevance
“…Resulting values for σ B direct presented here are similar to the one reported for Storglaciären (Jansson, 1999), but significantly smaller compared to the majority of all measured glaciers worldwide (e.g., Thibert et al, 2008;Beedle et al, 2014;Andreassen et al, 2015). This can be explained by the fact that the density of winter and summer point measurements is comparatively much more complete and substantially higher for our study glaciers than for most other glaciers (Supplementary Tab.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Resulting values for σ B direct presented here are similar to the one reported for Storglaciären (Jansson, 1999), but significantly smaller compared to the majority of all measured glaciers worldwide (e.g., Thibert et al, 2008;Beedle et al, 2014;Andreassen et al, 2015). This can be explained by the fact that the density of winter and summer point measurements is comparatively much more complete and substantially higher for our study glaciers than for most other glaciers (Supplementary Tab.…”
supporting
confidence: 82%
“…mass changes computed over pentadal to decadal time periods based on high-resolution source data (e.g. Andreassen et al, 2015;Magnússon et al, 2016).…”
mentioning
confidence: 99%
“…It was concluded that all the bedload together with most of the sand fraction of the suspended load was being deposited there. Andreassen et al (2004) found a significant correlation between the mass balances of Tunsbergdalsbreen and Nigardsbreen. It is thus reasonable to expect that also Tunsbergdalsbreen will respond to climatic change in the same way as Nigardsbreen.…”
mentioning
confidence: 84%
“…Geodetic determination of storage change in glaciers based on DEM differencing may be better than ±150 mm (Abermann and others, 2010; Bollmann and others, 2011); conventional glacier mass balances may have errors of 100–200 mm (e.g. Andreassen and others, 2015). The contribution of these uncertainty values to overall uncertainty is distinctly reduced by the ratio between glacierized to total area.…”
Section: Methodsmentioning
confidence: 99%